Ownership change and its implications for the match between the plant and its workers - Ragnhild Balsvik; Stefanie A. Haller (University College Dublin, UCD School of Economics, 2015)
Is ownership change an opportunity for new owners to make systematic changes in the workforce of the acquired plant? This paper explores the adjustments to plant size and the composition of the workforce that occur around ownership change using matched employer-employee data. Furthermore, we explore changes in the workforce along unobservable dimensions of worker quality and the quality of the match between the plant and its workers. We observe excess labour turnover around ownership change, but only in the case of foreign acquisitions do we find an improvement in unobserved worker and match quality at the plant level.
Keywords: F66; F23; J20; 330; ownership change; matched employer-employee data; multinationals; worker reallocation; unobserved fixed effects